Characterization of fecal microbiota across seven Chinese ethnic groups by quantitative polymerase chain reaction. - Lai-yu Kwok; Jiachao Zhang; Zhuang Guo; Qimu Gesudu; Yi Zheng; Jianmin Qiao; Dongxue Huo; Heping Zhang (PLoS ONE)
The human gut microbiota consists of complex microbial communities, which possibly play crucial roles in physiological functioning and health maintenance. China has evolved into a multicultural society consisting of the major ethnic group, Han, and 55 official ethnic minority groups. Nowadays, these minority groups inhabit in different Chinese provinces and some of them still keep their unique culture and lifestyle. Currently, only limited data are available on the gut microbiota of these Chinese ethnic groups. In this study, 10 major fecal bacterial groups of 314 healthy individuals from 7 Chinese ethnic origins were enumerated by quantitative polymerase chain reaction. Our data confirmed that the selected bacterial groups were common to all 7 surveyed ethnicities, but the amount of the individual bacterial groups varied to different degree. By principal component and canonical variate analyses of the 314 individuals or the 91 Han subjects, no distinct group clustering pattern was observed. Nevertheless, weak differences were noted between the Han and Zhuang from other ethnic minority groups, and between the Heilongjiang Hans from those of the other provinces. Thus, our results suggest that the ethnic origin may contribute to shaping the human gut microbiota.